Update on the applications and limitations of alpha-fetoprotein for hepatocellular carcinoma - Hanif, Hira; Ali, Mukarram Jamat; Susheela, Ammu T; Khan, Iman Waheed; Luna-Cuadros, Maria Alejandra; Khan, Muzammil Muhammad; Lau, Daryl Tan-Yeung (World journal of gastroenterology : WJG, 2022)
Alpha-fetoprotein (AFP) is an oncofetal glycoprotein that has been used as a tumor marker for hepatocellular carcinoma (HCC) in combination with ultrasound and other imaging modalities. Its utility is limited because of both low sensitivity and specificity, and discrepancies among the different methods of measurements. Moreover, its accuracy varies according to patient characteristics and the AFP cut-off values used. Combination of AFP with novel biomarkers such as AFP-L3, Golgi specific membrane protein (GP73) and des-gamma-carboxyprothrombin significantly improved its accuracy in detecting HCC. Increased AFP level could also signify severity of hepatic destruction and subsequent regeneration and is commonly observed in patients with acute and chronic liver conditions and cirrhosis. Hereditary and other non-hepatic disorders can also cause AFP elevation.